Boosting Cafe Service Quality: How Total Quality Management Empowers a Case Study at Konaro Coffee & Eatery, Bandung - Ester Manik; Iwan Sidharta; Kadir Kadir; Boy Suzanto; Nenny Rinawati; Retno Resawati; Elza Nurhaliza Hayat; Santi Despila; Rindu Jasun Arifin; Fajar Mulqi Fath; Tri Puji Citasari (LPPM STMIK Mardira Indonesia, 2025)
Intense competition in Bandung’s culinary industry forces coffee shops to maintain high service standards, yet many businesses like Konaro Coffee & Eatery still face operational inconsistencies that hinder optimal customer satisfaction. This applied research and community service initiative aims to identify these service quality bottlenecks and offer strategic solutions through the framework of Total Quality Management (TQM). The research team, comprising lecturers and students, employs a qualitative approach to investigate the cafe’s current service performance. We gathered primary data through in-depth interviews and field observations involving the cafe owners and operational staff as key informants. To analyze the data, we map the identified service issues directly against the core pillars of TQM, focusing on continuous improvement and process standardization. The study reveals that implementing a structured TQM framework successfully eliminates service delays, standardizes product consistency, and elevates the staff's hospitality skills. Consequently, these findings imply that adopting TQM principles not only resolves immediate operational gaps but also provides Konaro Coffee & Eatery with a sustainable competitive advantage in a crowded market.